(untitled) (Cardiovascular Journal, 2018)
Background: Octogenarians are high risk patients and largely under-represented in clinical trials. The use of evidence-based therapy is, therefore, lower in this age group, resulting in a reliance on non-evidence based decision making. The elderly usually have higher prevalence of co morbidities and more often experience complications during and after revascularization procedures. Methods: 212 patients with ischemic heart disease who underwent percutaneous coronary intervention (PCI) were divided into 2 groups according to age: ³80 years (n = 74) and < 80 years (n = 138). Baseline clinical characteristics, indications for coronary intervention, in hospital outcomes and 1 year outcome were obtained. Study endpoint was in hospital outcome (Renal impairment, MI, LVF, emergency revascularization, death) & 1 year follow up for myocardial infarction (MI), repeat revascularization and death. Results: Procedural success (TIMI III) were high in both groups, but still lower in the elderly as compared to younger group (95% vs. 97%, p=0.65).The elderly had higher incidence of post PCI bleeding, contrast induced nephropathy (CIN), MI, left ventricular failure (LVF) and death (9.5% vs.6.1%, 8.2% vs.3.7%, 6.8% vs.5.8%, 9.5% vs. 5.1% and 5.4%vs.3.6%, p=0.07). Whereas emergency revascularization were higher in younger group (5.4% vs. 6.5%, p=0.07). At 1 year MI and death were higher in elderly group (9.5% vs.6.5%, 6.8% vs.6.5% p=0.66), whereas repeat revascularization were higher in younger group (6.8% vs.8%, p= 0.66). Conclusion: Though immediate interventional procedure related complications are more in octogenarians, long term outcomes seem to be promising & comparable with younger counterparts. Cardiovasc. j. 2018; 10(2): 121-125